Collective Memory Of The Holocaust And National Identity Of the Students Youth In Ukraine - Ivanova, Olena (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The goal of this article was to explore collective memory of the Holocaust and its connections with the national identity in the students youth of Ukraine. A theoretical analysis of the concepts of collective memory and national identity and their characteristics was conducted. Writing essays as a methodology of collecting empirical data was provided and sample peculiarities were described. Discourse analysis was chosen as a methodology of empirical data analysis. It was proved that one can make some suggestions about national identity on the basis of collective memory. Civil, ethnic and victimized types of identity which have regional peculiarities were singled out.